Botanical remains from a coprolite from the Pleistocene hominin site of Malapa, Sterkfontein Valley, South Africa - Bamford, M.K.; Neumann, F.H.; Pereira, L.M.; Scott, L.; Dirks, P.H.G.M.; Berger, L.R. (Bernard Price Institute for Palaeontological Research, University of the Witwatersrand, 2010)
A coprolite probably from a carnivore described in this paper was recovered from the decalcified sediments of Facies D, close to the cranium of a hominid child, Australopithecus sediba, at Malapa, and is dated at 1.95–1.78 Ma based on a combination of faunal, U-Pb and palaeomagnetic dating techniques. Maceration of the coprolite yielded wood fragments and pollen of Podocarpus sp. as well as phytolith morphotypes that occur in leaves of Podocarpus and many other woody taxa. The Malapa site today is in the Grassland Biome, close to the transition to the Savanna Biome. Podocarpus/Afrocarpus occurs about 30km distance in the Northern Afromontane Forest Biome and is restricted to small patches in the mountain kloofs or small canyons (altitude: 1500–1900 m). The occurrence of this vegetation at Malapa in the past implies that the cooler, moister forest vegetation was more widespread.
Keywords: Podocarpus; pollen; wood; phytoliths